Common Fixed Point Theorems Satisfying Contractive Type Conditions in Complex Valued Metric Spaces - Uma. M, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
In this paper we prove common fixed point theorems satisfying contractive conditions involving rational expressions and product for four mappings that satisfy property (E.A) along with weak compatibility of pairs are proved property are obtained in complex valued metric spaces which generalize various results of ordinary metric spaces